After the end of art contemporary art and the pale of history - Danto, Arthur C. 1924-2013 (A.W. Mellon lectures in the fine arts, 1997)
Over a decade ago, Arthur Danto announced that art ended in the sixties. Ever since this declaration, he has been at the forefront of a radical critique of the nature of art in our time. After the End of Art presents Danto's first full-scale reformulation of his original insight, showing how, with the eclipse of abstract expressionism, art has deviated irrevocably from the narrative course that Vassari helped define for it in the Renaissance. Moreover, he leads the way to a new type of criticism that can help us understand art in a posthistorical age - where, for example, an artist can produce a work in the style of Rembrandt to create a visual pun, and where traditional theories cannot explain the difference between Andy Warhol's Brillo Box and the product found in the grocery store. Here we are engaged in a series of insightful and entertaining conversations on the most relevant aesthetic and philosophical issues of art, conducted by an especially acute observer of the art scene today. Originally delivered as the prestigious Mellon Lectures on the Fine Arts, these writings cover art history, pop art, "people's art," the future role of museums, and the critical contributions of Clement Greenberg - who helped make sense of modernism for viewers over two generations ago through an aesthetics-based criticism.